2012
DOI: 10.3791/3742
|View full text |Cite
|
Sign up to set email alerts
|

A Polished and Reinforced Thinned-skull Window for Long-term Imaging of the Mouse Brain

Abstract: In vivo imaging of cortical function requires optical access to the brain without disruption of the intracranial environment. We present a method to form a polished and reinforced thinned skull (PoRTS) window in the mouse skull that spans several millimeters in diameter and is stable for months. The skull is thinned to 10 to 15 μm in thickness with a hand held drill to achieve optical clarity, and is then overlaid with cyanoacrylate glue and a cover glass to: 1) provide rigidity, 2) inhibit bone regrowth and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 28 publications
1
105
0
Order By: Relevance
“…Thus, measurements to ascertain the precise spatial geometry of the vibrissa field are necessary when measurements, stimulation or injections in specific columns are required. A common and non-invasive method to map the vibrissa field is to image the evoked intrinsic optical signal (eIOS) [23 -25] through a cranial window [26] or thinned transcranial window [27,28]. The eIOS, like the blood oxygen level-dependent (BOLD) functional magnetic resonant image (fMRI) signal [29,30], exploits the change in electronic structure of haemoglobin that occurs when heme transitions from the oxidized to reduced, or deoxygenated, state [31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, measurements to ascertain the precise spatial geometry of the vibrissa field are necessary when measurements, stimulation or injections in specific columns are required. A common and non-invasive method to map the vibrissa field is to image the evoked intrinsic optical signal (eIOS) [23 -25] through a cranial window [26] or thinned transcranial window [27,28]. The eIOS, like the blood oxygen level-dependent (BOLD) functional magnetic resonant image (fMRI) signal [29,30], exploits the change in electronic structure of haemoglobin that occurs when heme transitions from the oxidized to reduced, or deoxygenated, state [31].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, it may ultimately be more beneficial to thin the cranium significantly and then cover with a nc-YSZ implant, as Shih et al recently demonstrated for glass-based implants. 13 Although beyond the scope of the current study, it is important to also briefly consider the effect of the scalp on imaging performance, since: a) coverage of the nc-YSZ implant with native scalp will be preferred for applications requiring long-term implantation; and b) repeated scalp removal is unlikely to be desirable when chronically-recurring access over large areas is required. Optical clearing agents (OCAs) represent a compelling possibility in this regard, since they have been shown to provide capability for temporarily rendering skin transparent on demand.…”
Section: Discussionmentioning
confidence: 99%
“…A pair of thin-skull transcranial windows, each over an area of 2.5 mm by 2.5 mm that spanned the parietal region of each hemispheres, were prepared by an extension of previous described procedures [12,29]. A drop of cyanoacrylate glue (no.…”
Section: Mouse Surgerymentioning
confidence: 99%